Satisfaction with the vine, attitudes towards buying and attitudes towards debt - Godoy B., María Pía (2015)
This study aimed to identify the presence of relationship between satisfaction with life, attitudes towards Purchase and consumption, and attitudes towards debt. The sample was composed by 744 persons from the city of Temuco and commune of Padre Las Casas, who were administered the scale of satisfaction with life, the scale of attitudes toward debt and the attitudes toward consumption and purchase scale. The results show that a higher level of satisfaction with life is related directly with to austere attitudes toward debt and attitudes towards rational purchase. It is also reported that a low level of satisfaction with life correlated inversely with attitudes toward compulsive, impulsive and hedonistic purchase.